Direct growth of few-layer graphene on AlN-based resonators for high-sensitivity gravimetric biosensors - Olivares, Jimena; Mirea, Teona; Gordillo-Dagallier, Lorena; Marco, Bruno; Escolano, José Miguel; Clement, Marta; Iborra, Enrique (Beilstein Journal of Nanotechnology, 2019)
We present the successful growth of few-layer graphene on top of AlN-based solidly mounted resonators (SMR) using a low-temperature chemical vapour deposition (CVD) process assisted by Ni catalysts, and its effective bio-functionalization with antibodies. The SMRs are manufactured on top of fully insulating AlN/SiO2 acoustic mirrors able to withstand the temperatures reached during the CVD growth of graphene (up to 650 °C). The active AlN films, purposely grown with the c-axis tilted, effectively excite shear modes displaying excellent in-liquid performance, with electromechanical coupling and quality factors of around 3% and 150, respectively, which barely vary after graphene integration. Raman spectra reveal that the as-grown graphene is composed of less than five weakly coupled layers with a low density of defects. Two functionalization protocols of the graphene are proposed. The first one, based on a covalent binding approach, starts with a low-damage O2 plasma treatment that introduces a controlled density of defects in graphene, including carboxylic groups. After that, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride/N-hydroxysuccinimide (EDC/NHS) chemistry is used to covalently bind streptavidin molecules to the surface of the sensors. The second functionalization protocol is based on the non-covalent bonding of streptavidin on hydrophobic graphene surfaces. The two protocols end with the effective bonding of biotinylated anti-IgG antibodies to the streptavidin, which leaves the surface of the devices ready for possible IgG detection.
Keywords: biomolecule detection; graphene integration; gravimetric biosensor; surface functionalization